Thermal behavior prediction and adaptation analysis of a reelwell drilling method for closed-loop geothermal system. (15th August 2022) - Yang, Hongwei; Li, Jun; Zhang, Hui; Jiang, Jiwei; Guo, Boyun; Gao, Reyu; Zhang, Geng
Highlights: A reelwell drilling method is proposed for temperature-controlled drilling. An integrated transient heat transfer model is developed for reelwell drilling. Reelwell drilling has a range of controllable parameters for wellbore temperature. The circulating mode B of reelwell drilling is suitable for geothermal reservoirs. Abstract: The ultra-high temperature characteristic of the deep closed-loop geothermal system poses a great challenge for drilling. This paper proposes a reelwell drilling method for temperature-controlled drilling in ultra-high temperature geothermal reservoirs. Combining the flow characteristics and heat transfer mechanisms in each flow channel under three circulating modes of reelwell drilling, a set of integrated transient heat transfer models is developed for distinct thermal-associated regions. The model simultaneously couples the effect of the variable temperature-mass flow resulting from the fluid transition in different flow channels. The finite difference method is used to solve the model, and the field measurement data is employed to validate the model. The heat transfer rate and wellbore temperature distribution in reelwell drilling are investigated, and the optimum circulating mode suitable for temperature-controlled drilling is optimized. The results indicate that the cumulative bottomhole heat flux is always negative in reelwell drilling, revealing that the bottomhole temperature decreases gradually. Additionally, the absolute values of the cumulative heat flux under different circulating modes are consistent with circulating mode B > conventional drilling > circulating mode C > circulating mode A. Thus, the circulating mode B can effectively reduce the bottomhole temperature during drilling directional well. Moreover, when a suitable dual-channel valve position is selected in the middle and lower part of the wellbore and the auxiliary fluid inlet temperature is controlled to be less than 20 °C, the circulating mode B has the best temperature-controlled effect. Therefore, the circulating mode B of reelwell drilling method can provide a new option for temperature-controlled drilling for the deep closed-loop geothermal system.